2011
DOI: 10.1111/j.1467-7687.2011.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Early sex differences in weighting geometric cues

Abstract: When geometric and non-geometric information are both available for specifying location, men have been shown to rely more heavily on geometry compared to women. To shed insight on the nature and developmental origins of this sex difference, we examined how 18- to 24-month-olds represented the geometry of a surrounding (rectangular) space when direct non-geometric information (i.e. a beacon) was also available for localizing a hidden object. Children were tested on a disorientation task with multiple phases. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 80 publications
2
18
0
Order By: Relevance
“…Importantly, in a similar experiment, when a feature wall was used, the sex difference went away and both men and women encoded the geometry of the space (Kelly & Bischof, 2008). Lourenco, Addy, Huttenlocher and Fabian (2011) found similar results with toddlers. In a real-world version of the task with an enclosed rectangular search space and either a unique hiding container or a distinctive flag placed on top of the target container, toddlers learned to reorient.…”
Section: Beacon Cues and Geometric Cuesmentioning
confidence: 75%
See 1 more Smart Citation
“…Importantly, in a similar experiment, when a feature wall was used, the sex difference went away and both men and women encoded the geometry of the space (Kelly & Bischof, 2008). Lourenco, Addy, Huttenlocher and Fabian (2011) found similar results with toddlers. In a real-world version of the task with an enclosed rectangular search space and either a unique hiding container or a distinctive flag placed on top of the target container, toddlers learned to reorient.…”
Section: Beacon Cues and Geometric Cuesmentioning
confidence: 75%
“…However, some geometric information may exist even when geometry-only tests are failed. Lourenco et al (2011) included conflict trials designed to assess the relative use of geometric and feature cues. All toddlers preferred the beacon cue to geometry, and all toddlers, both boys and girls, were slower to respond on the conflict trials than they had been during training.…”
Section: Beacon Cues and Geometric Cuesmentioning
confidence: 99%
“…When geometric and non-geometric objects are both available for specifying location, men have been shown to rely more heavily on geometry compared to women and the sex differences in object location were also reported in young children with boys relied more heavily than girls on geometry to guide localization. 53 Sex differences in the object recognition memory are also related to the type of objects. For example, studies found that men are usually more affective by plants whereas women are more sensitive with animals.…”
Section: Typical Female-favored Memorymentioning
confidence: 99%
“…In contrast, young children fail to navigate by landmark representations on a map when the landmark serves as an indirect cue to a hidden object and therefore must be combined with geometric information (Rutland, Custance, & Campbell, 1993; Shusterman, et al, 2008). Indeed, both children and adults show higher sensitivity to geometric information when maps are devoid of such landmarks than when they contain them (Dehaene, Izard, Pica, & Spelke, 2006; Shusterman, et al, 2008): representations of the geometry of the layout and of individual landmark objects may be mutually competitive (Lourenco, Addy, Huttenlocher & Fabian, 2011). …”
mentioning
confidence: 99%